Gout As a Predictor of Total Knee Arthroplasty Outcomes and Costs - Rosas, Samuel; Zuskov, Andrey; Luo, Tianyi David; Roche, Martin W.; Emory, Cynthia L.; Plate, Johannes F. (The Journal of Knee Surgery, 2020)
Gout is the most common inflammatory arthritis and affects approximately 4% of the U.S. population. As the prevalence of gout and the number of total knee arthroplasties (TKAs) performed continue to increase, the literature on TKA in patients with gout remains scant. The purpose of this study was to evaluate the outcomes of patients with gout following TKA at a population level, that is, how patient with gout fair after TKA. We hypothesized that patients with gout have higher rates of complications and higher costs compared with controls. A case–control study was designed to evaluate two cohorts of Medicare patients who underwent TKA whose only distinguishing feature was the presence or absence of gout. Matching was performed to decrease confounding at a 1:1 ratio based on age, gender, and Charlson comorbidity index (CCI), (10-year survival predictor). The Medicare standard analytical files were queried through International Classification of Disease and current procedural terminology codes. A total of 15,238 patients were evaluated with 7,619 in each cohort. There were no age, gender, or CCI differences and 57.4% were females. Day of surgery and 90-day post-surgery costs were both significantly greater in those with gout (p < 0.001 for both). Multivariate analysis revealed that gout patients had increased odds of infection (odds ratio [OR] 1.229, p = 0.019), cardiac arrest (OR 1.354, p = 0.002), pneumonia (OR 1.161, p < 0.001), hematoma (OR 1.204, p = 0.002), and development of capsulitis (OR 1.208, p = 0.012). Nonetheless these patients had a decreased risk of pulmonary emboli (OR 0.835, p = 0.016). Our results support our hypothesis that patients with gout have higher rates of postoperative complications and increased day of surgery and 90-day costs of care after TKA. Given the high prevalence of gout in the United States, additional study on the utility of preoperative gout optimization for TKA patients is warranted. The level of evidence of this study is III, and it is a retrospective case–control study.
Keywords: gout; arthroplasty; costs; Charlson comorbidity index